Dynamics of National Budget of Lithuania - Bivainis, Juozas; Mitkevičius, Rimantas (Ekonomika, 2003)
This paper presents the dynamics of National budget of the Republic of Lithuania in 1993-2002, the main tendencies of fluctuation budget rates and the reason.. of this fluctuations. Section one reviews the dynamics of the most general National budget rates which arc compared to consolidated general governmental operation and gross domestic product. The circumstantial vertical comparative analysis of the examined period revenue (by hands and tax types) and expenditure (by function of government) is carried out in second and third sections.The results of the research showed that Lithuanian national budget, which makes up more than 21 3 consolidated budget of country by revenue and expenditure rates, exceeded the 10-billion limit. More than 20 percent of made-up gross domestic products redistributed by it. So possible precondition that disclosed the consistency of the country national budget rates in 1993-2002 and current tendencies reflect the development of countries social and economic policy in the last decade.The utmost significance of National budget revenue and expenditure rates increased fourfold during the period of 1993-2002, but there is a distinctly visible consistent tendency - the decline of their ratio as a percentage of gross domestic product. Such tendency undoubtedly proclaims the declines of government redistribution role, contrary to mass media estimation. The Lithuanian national budget absolutely is applicable to deficit range (the revenue exceeded expenditure only in 1993).The dynamics of the examined period National budget revenue and expenditure rates (not only general but also sectional) visibly shows two different development stages: fast enough and rising permanently absolute significance rates in 1993-1998 and greater variety its in 1999-2002. The typical instance of the latter is the decline of rates in 1999-2000 and revitalization tendencies in 2001-2002. These fluctuations concern directly with both, the decline of Lithuanian economy due to outcomes of Russian financial crisis which is widely investigated and inefficient economic policy decisions.During the examined decade there were no more substantial changes in the structure of National budget revenue by hands and tax revenue institute 87.4 percent of total state revenue (2001). Some more considerable fluctuations of revenue structure took place only during certain years. In general these cases were conditioned by reclassification, decomposition and replenishment the tax and nontax revenue hands. More considerable changes are characteristic feature for internal structure the tax revenue: increase of the relative ratio of VAT and excises and decrease of tax on corporate profits. The biggest part of these changes took place during the period of 1993-1997, later the changes of tax revenue internal structure have become of the evolutionary character.The analysis of National budget expenditure shows that according to the function of government the structure of budget can be characterized by the following tendencies: decrease of the relative ratio of the expenditure on the economy when in absolute terms it stays on initial level. increase of the relative ratio of expenditure on other functions of government as well as its absolute dimension, increase of absolute dimension expenditure on social affairs when its relative share in total National budget expenditure during examined period (1993-2002) remained stable enough. These tendencies are explained in a more detailed way by examination the internal structure and dynamics of the expenditure for each function of government.